Application of COBIT 5 Framework in the Evaluation of Information Technology Infrastructure to Improve Education Effectiveness (Case Study of SMK YPT Pringsewu) - Agus Ginanjar; Ochi Marshella Febriani (Jurnal Teknoinfo, 2026)
The development of information technology (IT) in the world of education requires educational institutions to have effective and structured IT infrastructure governance. SMK YPT Pringsewu as a technology-based vocational school faces various problems related to IT infrastructure, especially in computer and network laboratories, such as inadequate device specifications, unstable internet connections, and suboptimal system management and monitoring. This study aims to evaluate the condition of information technology infrastructure in supporting the effectiveness of education using the ISACA framework, namely COBIT 5. This study uses a quantitative approach with a survey method through the distribution of questionnaires to 227 respondents consisting of students and teachers majoring in DKV and TKJ. The domains used in the evaluation are DSS01 (Manage Operations), BAI02 (Manage Requirements Definition), and MEA01 (Monitor, Evaluate and Assess Performance and Conformance). The analysis was carried out by measuring the maturity level based on the COBIT 5 capability model and conducting gap analysis between the current conditions and the expected conditions. The results show that the level of maturity of IT infrastructure governance at SMK YPT Pringsewu is at the Defined Process level (Level 3), but there are still some gaps in aspects of operational management, performance monitoring, and definition of IT needs. Therefore, improvements are needed in the form of the preparation of more structured standard operating procedures, improved device maintenance, optimization of infrastructure monitoring, and more targeted IT development planning. This research is expected to be a reference for SMK YPT Pringsewu in increasing the effectiveness of IT infrastructure management and supporting the improvement of the quality of the learning process.